1998
DOI: 10.1111/j.1439-0434.1998.tb04687.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed Bacterization with Bacillus subtilis AF 1 Increases Phenylalanine Ammonia‐lyase and Reduces the Incidence of Fusarial Wilt in Pigeonpea

Abstract: Cell free culture filtrate of a biocontrol PGPR strain of Bacillus subtilis showed a concentration-dependent growth and conidiation inhibition of Fusarium udum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 27 publications
8
34
0
3
Order By: Relevance
“…Este efeito inibitório pode estar relacionado com a produção de quitinases e de outras enzimas que podem ter ação contra a parede celular fúngica, já que algumas bactérias antagonistas de fungos fitopatogênicos podem produzir quitinases (Mavingui & Heulin, 1994). Também foi observado que o Bt possui atividade quitinolítica (Barbosa-Corona et al, 1999;Rojas-Avelizapa et al, 1999), porém, estes autores estavam buscando fatores de patogenicidade contra insetos, e não, contra fungos fitopatogênicos.…”
Section: Fungistatic Effect Of Bacillus Thuringiensis and Of Other Baunclassified
See 1 more Smart Citation
“…Este efeito inibitório pode estar relacionado com a produção de quitinases e de outras enzimas que podem ter ação contra a parede celular fúngica, já que algumas bactérias antagonistas de fungos fitopatogênicos podem produzir quitinases (Mavingui & Heulin, 1994). Também foi observado que o Bt possui atividade quitinolítica (Barbosa-Corona et al, 1999;Rojas-Avelizapa et al, 1999), porém, estes autores estavam buscando fatores de patogenicidade contra insetos, e não, contra fungos fitopatogênicos.…”
Section: Fungistatic Effect Of Bacillus Thuringiensis and Of Other Baunclassified
“…Inúmeras espécies deste gênero já demonstraram atividade antifúngica (Kim et al, 1997;Podile & Laxmi, 1998) …”
Section: Fungistatic Effect Of Bacillus Thuringiensis and Of Other Baunclassified
“…A study has indicated that total phenol contents (TPCs) were significantly higher in resistant varieties compared to the susceptible ones to Alternaria triticina (Mishra et al, 2011). Phenylalanine ammonialyase (PAL) being the first step in the phenylpropanoid biosynthesis pathway, also plays an important role in biosynthesis of the different families of phenolics (coumarins, flavonoids, lignins), phenolic derivatives and its activity being correlated with the level of synthesis of the phenolic compound (Podile, Laxmi, 1998). The induction of PAL activity preceding an increase in the Biochemical and histochemical parameters associated with slow blighting of spot blotch (Bipolaris sorokiniana (Sacc.…”
Section: Introductionmentioning
confidence: 99%
“…PAL activity was significantly higher for the UFV 252 and UFV 592 treatments at 0 dai, for the UFV 252, UFV 592 and UFV592 treatments at 2 dai and only for the UFV 252 treatment at 7 dai compared to the control treatment (Figure 4a). PAL is important for phenolic compound synthesis in the phenylpropanoid pathway, and also plays a crucial role in lignin and flavonoid biosynthesis (Podile and Laxmi, 1998). For at least one evaluation time, PAL activity was higher for the plants treated with the antagonists UFV 618, UFV 592 and UFV 252.…”
Section: F Valuesmentioning
confidence: 98%
“…The induced resistance triggered by biological and chemicals inducers is due to an increase in the activities of several enzymes (Shanmugam and Kanoujia, 2011;Van Loon, 2007), such as the lipoxygenases, which contribute to the production of jasmonic acid during lipid peroxidation in the plasma membrane (Schaller and Stintzi, 2009), peroxidases and polyphenoloxidases, which together mediate lignin production (Campbell and Sederoff, 1996), and phenylalanine ammonia-lyases,which participate in the biosynthesis of phenolic compounds in the phenylpropanoid pathway (Podile and Laxmi 1998). The hydrolytic enzymes chitinases and β-1,3-glucanases degrade fungal cell walls, and the released oligosaccharides elicit defense responses against the pathogen attack (Roberts and Selitrennikoff, 1988).…”
Section: Introductionmentioning
confidence: 99%